Evaluation of herbicides combination for effective weed control in groundnut: INTEGRATED WEED MANAGEMENT IN GROUNDNUT - T PARTHIPAN; C HARISUDAN (Journal of Oilseeds Research, 2020)
Groundnut is highly susceptible to weed infestation because of its slow growth at initial stages up to 40 DAS and the weeds interfere with pegging, pod development and harvesting of groundnut at different crop growth stages besides competing for essential resources. Yield losses due to weeds have been estimated as high as 24 to 70% in groundnut. Therefore, weeding has to be completed before pegging. Major problemin agriculture is labour shortage during the peak period of important operations like sowing, weeding and harvesting. The manual method of weed control is costly and time consuming as well as need to be repeated at frequent intervals. In this context, chemical weed control is a better supplement to conventional methods. Hence, field experiments were conducted at Regional ResearchStation, Tamil Nadu Agricultural University, Vridhachalamduring kharif 2018 and kharif 2019 to evaluate suitable herbicide combinations for effective weed control and reducing labour consumption in groundnut production. The experiment was laid out in a randomized complete block design replicated thrice with nine treatments. Pre-emergence application of Pendimethalin 30 EC + Imazethapyr 2 EC @ 1.0 kg/ha (ready mix) followed by one manual weeding at 25-30 DAS showed higher weed control efficiency (67.37 %) followed by two manual weedings at 20 and 40 DAS (61.37%) and pre-emergence application of Pendimethalin @ 1.0 kg/ha + Manual weeding at 25-30 DAS (60.30%). Significantly higher pod yield (2400 kg/ha) was recorded by pre-emergence application of Pendimethalin 30 EC + Imazethapyr 2 EC @ 1.0 kg/ha (ready mix) followed by one manual weeding at 25-30 DAS, whereas pre-emergence application ofPendimethalin@1.0 kg/ha+Manual weeding at 25-30 DAS recorded pod yield of 2067 kg/ha only which was at par with two manual weedings at 20 and 40 DAS (1967 kg/ha).